RE-ENGINEERING OF HUMAN RESOURCES TO IMPROVE THE PERFORMANCE. (MARKETING DEPARTMENT OF PT KERTAS LECES (PERSERO) PROBOLINGGO, EAST JAVA. - Haris, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Research Reengineering human resources to improve its performance (marketing department pt. Kertas leces (persero) Probolinggo East Java). Research approach with qualitative. The data method used in this study is SWOT. SWOT is a tool used to compile the company’s strategic factors. The research sample was conducted on human resources employees related to the transaction function, scrambling function, management function and marketing planning function. The results of the study stated that the results of the evaluation of Human Resources Re-engineering in the Marketing Department of PT Kertas Leces (Persero) after being evaluated using Ishikawa Diagrams and SWOT Analysis there are many or almost all of the functions that there are many weaknesses and even below 50% performance against the standard.